NK cells modulate in vivo control of SARS-CoV-2 replication and suppression of lung damage. - Harikrishnan Balachandran; Kyle Kroll; Karen Terry; Cordelia Manickam; Rhianna Jones; Griffin Woolley; Tammy Hayes; Amanda J Martinot; Ankur Sharma; Mark Lewis; Stephanie Jost; R Keith Reeves (PLoS Pathogens)
Natural killer (NK) cells play a critical role in virus control. However, it has remained largely unclear whether NK cell mobilization in SARS-CoV-2 infections is beneficial or pathologic. To address this deficit, we employed a validated experimental NK cell depletion non-human primate (NHP) model with SARS-CoV-2 Delta variant B.1.617.2 challenge. Viral loads (VL), NK cell numbers, activation, proliferation, and functional measures were evaluated in blood and tissues. In non-depleted (control) animals, infection rapidly induced NK cell expansion, activation, and increased tissue trafficking associated with VL. Strikingly, we report that experimental NK cell depletion leads to higher VL, longer duration of viral shedding, significantly increased levels of pro-inflammatory cytokines in the lungs, and overt lung damage. Overall, we find the first significant and conclusive evidence for NK cell-mediated control of SARS-CoV-2 virus replication and disease pathology. These data indicate that adjunct therapies for infection could largely benefit from NK cell-targeted approaches.